1999
DOI: 10.1182/blood.v94.2.765.414a29_765_772
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous High p27/KIP1 Expression in a Subset of Aggressive B-Cell Lymphomas Is Associated With Cyclin D3 Overexpression. p27/KIP1—Cyclin D3 Colocalization in Tumor Cells

Abstract: p27 cyclin-dependent kinase inhibitor downregulation is essential for transition to the S phase of the cell cycle. Thus, proliferating cells in reactive lymphoid tissue show no detectable p27 expression. Nevertheless, anomalous high p27 expression has been shown to be present in a group of aggressive B-cell lymphomas with high proliferation index and adverse clinical outcome. This suggests that abnormally accumulated p27 protein has been rendered functionally inactive. We analyzed the causes of this anomalous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
1
28
1
1
Order By: Relevance
“…This observation was in keeping with our results, which showed that a significant proportion (approximately 40%) of total p27 Kip1 protein was found in the cytoplasmic fraction of 6/11 of lymphoma cell lines. Previous laser confocal microscopy and co‐immunoprecipitation studies (Sanchez‐Beato et al , 1999) have shown the existence of cyclin D3/p27 Kip1 complexes within the nucleus of Burkitt lymphoma cells. Cytoplasmic displacement/sequestration of p27 Kip1 has been reported to be a potential mechanism of its inactivation (Barnouin et al , 1999).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This observation was in keeping with our results, which showed that a significant proportion (approximately 40%) of total p27 Kip1 protein was found in the cytoplasmic fraction of 6/11 of lymphoma cell lines. Previous laser confocal microscopy and co‐immunoprecipitation studies (Sanchez‐Beato et al , 1999) have shown the existence of cyclin D3/p27 Kip1 complexes within the nucleus of Burkitt lymphoma cells. Cytoplasmic displacement/sequestration of p27 Kip1 has been reported to be a potential mechanism of its inactivation (Barnouin et al , 1999).…”
Section: Discussionmentioning
confidence: 98%
“…A positive correlation between p27 Kip1 and cyclin D3 levels was observed in Jurkat and PB697 while a negative correlation was seen in HPB, Nalm‐6 and Raji cells. Sanchez‐Beato et al (1999) have previously demonstrated that cyclin D3/p27 Kip1 complexes within the nucleus are inactive in a subset of aggressive B lymphomas. Immunoprecipitation studies of seven cell lines with variable levels of p27 Kip1 expression, including three with high p27 Kip1 levels (Jurkat, CEM‐ and PB697) and low (NCEB) to minimal levels of p27 Kip1 (Raji, OCI LY‐1 and Nalm‐6), followed by immunoblotting with anticyclin D3 antibody (Fig 5C), demonstrated the presence of cyclin D3/p27 Kip1 complexes within both the nuclear and cytoplasmic fractions.…”
Section: Sequestration Of P27kip1 By Cyclin D3 In Both Nuclear and Cymentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulation in expressions of CDK inhibitors, such as p15 and p16, has also been shown to be involved in lymphomagenesis [21]. Tracing these trends, recent studies have focused on the involvement of the universal CDK inhibitor p27 in lymphomagenesis [12,13,22,23], because p27 is known to be an amount-dependent tumor-suppressive protein [6]. Indeed, a reduced intracellular concentration of p27 protein in cancer cells has been shown to correlate with poor prognosis [6,8], and the loss of p27 allele in mice increased the sensitivity of these animals to carcinogenic agents [24].…”
Section: Discussionmentioning
confidence: 99%